2014
DOI: 10.1089/scd.2013.0599
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of an Immortalized Human Mesenchymal Stromal Cell Line

Abstract: Human mesenchymal stromal cells (hMSCs) show great potential for clinical and experimental use due to their capacity to self-renew and differentiate into multiple mesenchymal lineages. However, disadvantages of primary cultures of hMSCs are the limited in vitro lifespan, and the variable properties of cells from different donors and over time in culture. In this article, we describe the generation of a telomerase-immortalized nontumorigenic human bone marrow-derived stromal mesenchymal cell line, and its detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 49 publications
3
51
0
Order By: Relevance
“…Increase in cancer antigen families in telomerized hMSC have been reported, including previous work from our group, which studied the tumorigenic hMSC‐TERT20 . In another study of telomerized hMSC, similar changes were observed. These cancer antigen gene functions are poorly understood, although they are frequently expressed in tumor or embryonic tissues but not in somatic tissues (as reviewed in Simpson and colleagues).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Increase in cancer antigen families in telomerized hMSC have been reported, including previous work from our group, which studied the tumorigenic hMSC‐TERT20 . In another study of telomerized hMSC, similar changes were observed. These cancer antigen gene functions are poorly understood, although they are frequently expressed in tumor or embryonic tissues but not in somatic tissues (as reviewed in Simpson and colleagues).…”
Section: Discussionsupporting
confidence: 68%
“…We have previously reported the generation and characterization of telomerized hMSC, which we termed hMSC‐TERT, and reported that telomerization abolished replicative senescence and not only maintained but enhanced bone formation capacity of the cells when implanted subcutaneously in immune‐deficient mice . Other investigators corroborated these findings (see summary of the telomerized cell lines in Table ). Telomerized hMSC are also good cellular models for primary hMSC because of their stable phenotype and are thus suitable for proteomic and genomic studies requiring the use of a large number of cells .…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Positive for ARS, APS, and Runx2 upregulation [71] Positive for ABS, TBS, and GAG assay in pellet culture [72]; low chondrogenic potential but stimulation of chondrocyte differentiation Positive for OROS, adipogenesis-related genes upregulation [71,73], and NRS [73] BMA13H Positive for ARS (reduced compared with primary cells) [74] Positive for ABS and GAG assay in 2D culture [74]; also positive for TBS, PSR and aggrecan and ColII immunostaining in 3D culture [75]; chondrogenic potential reduced compared with primary cells [74] Positive for OROS (reduced compared with primary cells) [74] SCP-1…”
Section: But Alsomentioning
confidence: 99%
“…Transduction of hTERT alone has been employed to generate iMSC lines, but, since hTERT has no effect over non-replicative senescence, it has also been reported to fail to immortalize MSCs derived from bone marrow [13,18,58,74,104] and adipose tissue [85]. Skårn et al (2014) described that only one out of nine hTERT-transduced bone marrow-derived MSC clones was able to proliferate over 40 PDs, and even this clone showed a slow proliferation rate similar to that of primary MSCs [71]. Other authors have confirmed that hTERT-transduced MSCs displayed a lifespan similar to that of primary MSCs (about 30-40 PDs) [18,81].…”
Section: Immortalizing Human Adult Mscsmentioning
confidence: 99%